Effects of parental emotional warmth on the relationship between regional gray matter volume and depression-related personality traits. (4th May 2017) - Yang, Junyi; Yin, Ping; Wei, Dongtao; Wang, Kangcheng; Li, Yongmei; Qiu, Jiang
ABSTRACT: The depression-related personality trait is associated with the severity of patients' current depressive symptoms and with the vulnerability to depression within the nonclinical groups. However, little is known about the anatomical structure associated with the depression-related personality traits within the nonclinical sample. Parenting behavior is associated with the depression symptoms; however, whether or not parenting behavior influence the neural basis of the depression-related personality traits is unclear. Thus in current study, first, we used voxel-based morphometry to identify the brain regions underlying individual differences in depression-related personality traits, as measured by the revised Neuroticism-Extraversion-Openness Personality Inventory, in a large sample of young healthy adults. Second, we use mediation analysis to investigate the relationship between parenting behavior and neural basis of depression-related personality traits. The results revealed that depression-related personality traits were positively correlated with gray matter volume mainly in medial frontal gyrus (MFG) that is implicated in the self-referential processing and emotional regulation. Furthermore, parental emotional warmth acted as a mediational mechanism underlying the association between the MFG volume and the depression-related personality trait. Together, our findings suggested that the family environment might play an important role in the acquisition and process of the depression-related personality traits.